Yersinia enterocolitica Infection in Patients Undergoing Intermittent Hemodialysis (Journal of Renal and Hepatic Disorders, 2020)
End-stage renal disease is the last stage of chronic kidney disease and affects more than 2 million patients worldwide. The infection-related hospitalization is an important cause of excess morbidity and mortality in this group of patients. Yersinia enterocolitica (YE) is one of the bacteria that hemodialysis (HD) patients can occasionally be infected with. The most common symptoms are fever and mild diarrhea, which is self-limited. However, in HD patients, especially in iron-overloaded cases, severe watery or bloody diarrhea can occur. The consumption of undercooked food by patients should sensitize the physician to the possibility of YE infection. Clinically, YE is difficult to diagnose due to nonspecific symptoms and the relatively low prevalence of yersiniosis, compared to other causative pathogens in dialysis patients. There is little information about yersiniosis in HD patients. For this reason, this review aims to summarize the current knowledge on YE infection in HD patients, with the main objective of expounding the problems in identifying, diagnosing, and treating yersiniosis in HD patients.
Keywords: end-stage renal disease; enteric yersiniosis; hemodialysis; Yersinia enterocolitica